2005
DOI: 10.1065/espr2005.08.280
|View full text |Cite
|
Sign up to set email alerts
|

Ah Receptor Agonists in UV-exposed Toluene Solutions of Decabromodiphenyl Ether (decaBDE) and in Soils Contaminated with Polybrominated Diphenyl Ethers (PBDEs) (9 pp)

Abstract: Bioassays are valuable for studying environmental transformation processes like this, where chemical analysis and subsequent toxicological evaluation requires available standard compounds and information on toxicological potency. The use of bioassays allows a rapid evaluation of toxicological relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…The present study should be related to few previous studies on photolysis of DecaBDE and/or BDE-209 (Watanabe and Tatsukawa 1987;Ohta et al 2001;Hua et al 2003;Söderström et al 2004;Bezares-Cruz et al 2004;Palm et al 2004;Eriksson et al 2004b;Hagberg et al 2006;Olsman et al 2006;Ahn et al 2006b). The first, performed in the late 1980s by Watanabe and Tatsukawa (Watanabe and Tatsukawa 1987), indicated the formation of debrominated diphenyl ethers.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…The present study should be related to few previous studies on photolysis of DecaBDE and/or BDE-209 (Watanabe and Tatsukawa 1987;Ohta et al 2001;Hua et al 2003;Söderström et al 2004;Bezares-Cruz et al 2004;Palm et al 2004;Eriksson et al 2004b;Hagberg et al 2006;Olsman et al 2006;Ahn et al 2006b). The first, performed in the late 1980s by Watanabe and Tatsukawa (Watanabe and Tatsukawa 1987), indicated the formation of debrominated diphenyl ethers.…”
mentioning
confidence: 81%
“…Also, the formation of PBDFs was confirmed under their photolytic experiment. Another few studies showed similar products being formed from BDE-209 (Bezares-Cruz et al 2004;Hagberg et al 2006;Olsman et al 2006). Degradation rates of 15 PBDE congeners, dissolved in 80% methanol exposed to UV light, were determined by Eriksson et al (2004b) showing decreasing rates with decreased bromination degree of the diphenyl ethers.…”
mentioning
confidence: 98%
“…Some waste types, such as electronic waste (e-waste) or car shredder waste material, were and continue to be highly contaminated with compounds such as PCBs, brominated flame retardants, brominated dibenzodioxins and dibenzofurans (PBDD/Fs) as well as toxic heavy metals (Meyer et al 1993;Olsman et al 2006;Secretariat Stockholm Convention 2006;Tasaki et al 2004;Five Winds 2001;US EPA 1991;UNEP 2005b;Weber and Kuch 2003;Wong et al 2007). As a result, the associated disposal sites and recycling areas can become highly contaminated if these activities are carried out without appropriate regulation and control.…”
Section: Contaminated Sites From Waste Management Deposition and Recmentioning
confidence: 99%
“…The samples were tested for AhR-mediated activities in the CALUX assay, a dioxin bioassay that utilizes H4IIE rat hepatoma cells stably transfected with a luciferase reporter gene (Murk et al 1996) according to the methods presented by Olsman et al (2005) and Gustavsson et al (2007). The cells were grown as monolayers in 10 ml of α-minimal essential medium (α-MEM, Sigma) supplemented with 10% sterile fetal calf serum (FCS, LabKemi) in culturing bottles.…”
Section: Calux Bioassay With H4iie Rat Hepatoma Cellsmentioning
confidence: 99%